An Automatic Watering System Based on an Arduino Microcontroller and Soil Moisture Sensors with Solar Panel Power Plant - Anugrah Rinasa Agistya; Sika Rino Rian; Sunardi; Marcell Telly (BIO Web of Conferences)
The large eggplant farming land often makes it difficult for farmers to water. In addition, the water content in the soil does not meet the minimum requirement, which is 80%-90%. Hence, adequate watering with a high level of accuracy is necessary. This study aims to design and invent an automatic watering system for eggplant farming land with an area of 150 m2. The method was to design automatic sprinklers using programming and fritzing software using Arduino IDE. Soil moisture data was obtained from the soil moisture sensor and displayed on the I2c LCD so that farmers could monitor the soil moisture level. The pump used PB-WH1100BCP with a specification of 1100 W with a discharge of 145 l/minute and a head of 30 m. This automatic watering system was supplied with a 500 Wp photovoltaic solar cell with a current value of 2 A, and a voltage of 20V was obtained when the sun was shining and could work effectively for 6 hours per day. To store electric current, this system was equipped with a VRLA 12V- 200Ah battery connected in series, and the current charging was controlled by the Solar Charge Controller (SCC). It can supply electric current to the pump for 24 hours. This automatic watering system has been tested and functions well on eggplant farmland.